JUUL on Twitter: Analyzing Tweets About Use of a New Nicotine Delivery System. (11th December 2019) - Sidani, Jaime E.; Colditz, Jason B.; Barrett, Erica L.; Chu, Kar‐Hai; James, A. Everette; Primack, Brian A.
ABSTRACT: BACKGROUND: Initial reports suggest that JUUL, a popular e‐cigarette, is being used in schools and other locations in which cigarette smoking is illegal or discouraged. However, there is little scholarly research documenting this. We aimed to make a systematic analysis of JUUL use themes and sentiment on Twitter. METHODS: Data were collected from Twitter's Filtered Streams Application Programming Interface from April 12, 2018 to May 10, 2018. This yielded 67, 934 tweets, from which a random sample of 2% was selected for coding. The final dataset included 1209 tweets. Inter‐rater reliability ranged κ = 0.64–0.85. RESULTS: The majority (71.5%) of tweets expressed positive sentiment toward JUUL. JUUL use in places where cigarette smoking is illegal or discouraged appeared in 111 tweets (9.2%); approximately one‐third of these tweets referring to using the device in school. Nearly 20% of tweets mentioned using the device at home and/or directly in front of responsible adults. CONCLUSIONS: This study confirms anecdotal reports of JUUL use in places where cigarette smoking is illegal or discouraged. Positive sentiment about use of JUUL suggests that the product is being normalized among young people. It may be valuable for educators to discuss the addictive nature of nicotine delivered through JUUL with younger populations.